Transgene Pyramiding of the HVA1 and mtlD in T3 Maize (Zea mays L.) Plants Confers Drought and Salt Tolerance, along with an Increase in Crop Biomass - Thang Xuan Nguyen; Truong Nguyen; Hussien Alameldin; Benjamin Goheen; Wayne Loescher; Mariam Sticklen (International Journal of Agronomy)
The pBY520 containing the Hordeum vulgare  HVA1 regulated by the rice actin promoter (Act1 5′) or the JS101 containing the bacterial mannitol-1-phosphate dehydrogenase (mtlD) also regulated by rice Act1 5′ and a combination of these two plasmids were transferred into the maize genome, and their stable expressions were confirmed through fourth generations. Plants transcribing a combination of the HVA1+mtlD showed higher leaf relative water content (RWC) and greater plant survival as compared with their single transgene transgenic plants and with their control plants under drought stress. When exposed to various salt concentrations, plants transcribing the HVA1+mtlD showed higher fresh and dry shoot and dry root matter as compared with single transgene transgenic plants and with their control plants. Furthermore, the leaves of plants expressing the mtlD accumulated higher levels of mannitol. Plants expressing the HVA1+mtlD improved plant survival rate under drought stress and enhanced shoot and root biomass under salt stress when compared with single transgene transgenic plants and with their wild-type control plants. The research presented here shows the effectiveness of coexpressing of two heterologous abiotic stress tolerance genes in the maize genome. Future field tests are needed to assure the application of this research.